The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/eva.13044
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the individual impact of artificial barriers in freshwaters: A standardized and absolute genetic index of fragmentation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…For instance, the temporal inertia in the establishment of genetic differentiation after barrier creation makes it particularly difficult to compare the impact of obstacles differing in age or in the effective size of the populations they separate. We developed a standardized index of genetic connectivity ( C INDEX ), allowing an absolute and independent assessment of the individual effects of obstacles on connectivity (Prunier et al, 2019). We demonstrated that the C INDEX , based on the comparison between observed and expected measures of genetic differentiation, allows quantifying genetic effects of fragmentation a few generations (~10 generations) after barrier creation, while allowing valid comparisons among species and obstacles of different ages.…”
Section: The Impacts Of Human Activities On Intraspecific Diversity Imentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the temporal inertia in the establishment of genetic differentiation after barrier creation makes it particularly difficult to compare the impact of obstacles differing in age or in the effective size of the populations they separate. We developed a standardized index of genetic connectivity ( C INDEX ), allowing an absolute and independent assessment of the individual effects of obstacles on connectivity (Prunier et al, 2019). We demonstrated that the C INDEX , based on the comparison between observed and expected measures of genetic differentiation, allows quantifying genetic effects of fragmentation a few generations (~10 generations) after barrier creation, while allowing valid comparisons among species and obstacles of different ages.…”
Section: The Impacts Of Human Activities On Intraspecific Diversity Imentioning
confidence: 99%
“…To warrant effective management prioritization and proper evaluation of restoration measures, it is crucial that environmental managers have access to precise and robust estimates of the individual impact of weirs and dams on functional connectivity. By introducing the C INDEX (Prunier et al, 2019), we aimed to tackle a number of technical issues stemming from the indirect quantification of barrier effects from genetic data, although we readily acknowledge that further developments are still needed to make it a fully operational tool. We notably plan to take into account the role of asymmetric gene flow (Paz‐Vinas et al, 2015) and to improve both spatial and temporal resolutions of the C INDEX by considering the use of genomic and epigenetic markers (Rey et al, 2020).…”
Section: The Impacts Of Human Activities On Intraspecific Diversity Imentioning
confidence: 99%
“…We preferred this metric of differentiation over other metrics (e.g., Fst, Gst, Jost’s D, etc.) as it has been shown to be robust to variations in mutation rates and sample sizes [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sampling operations ‘Before’ and ‘After’ restoration were performed using electrofishing, until a maximum of 30 adult individuals of each species were captured on either side of obstacles. Fish were captured in the direct downstream and upstream vicinity of each obstacle (Prunier et al, 2020), starting from the downstream site to avoid accidental upstream to downstream movements of individuals. A piece of pelvic fin was sampled on all individuals and stored in 96% alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we implemented a “before-after genetic monitoring” of the restoration of 11 weirs in France using a recently developed genetic index of fragmentation (the F INDEX ; Prunier et al, 2020). The F INDEX provides, independently for each obstacle, an absolute and standardized estimate of (species-specific) genetic connectivity, while taking into account two confounding factors: the age of the obstacle and the size of populations on either side of the obstacle.…”
Section: Introductionmentioning
confidence: 99%